Automatic control and supervision using PC based monitoring and control system (PCMOC system) for 5 stations production line - Ghazali, K. H.; Razali, Saifudin; Mohd Salmizan, Mohd Zain (2006)
Automatic control has played a vital role in the advance of engineering. The automatic system for manufacturing is a part of automatic control and becomes very important to industry in order to ensure the improvement of productivity. Small and medium industry (SMI) in Malaysia started their operation with traditional and conventional machine as well as using manual technology to produce a certain product. Most SMI in Malaysia did not optimize the use of technology in their production system. On top of that, this research will propose a very simple application to interface programmable logic controller (PLC) OMRON CQMIH with Visual Basic so that the users will be able to monitor and supervise the production line through PC in a control room. The graphical user interface (GUI) software has been developed using Visual Basic and successful communicate between PLC's hardware card. All the activities of production line including loading station, pressing station, centering station, inspecting station and sorting station can be monitor through PC by displaying all the components movement respected to PLC programs. Besides monitoring the system, the production application hardware can also be controlled by the software. As a result, this system can be implementing to optimize a production capability.